Bridging the Research Impact Divide: University Contributions to Community Well-Being in the Global South - Joshi, Surendra Prasad; Khatiwada, Padma Prasad (Tribhuvan University Journal, 2026)
Even though university research in Sustainable Development Goal (SDG) areas has grown by an order of magnitude since 2015, a gap remains between academic research and community outcomes, particularly in climate-vulnerable and resource-limited communities. This study employs a structured evidence-mapping and bibliometric analysis design, supplemented by thematic synthesis, to synthesize 80 sources from environmental science, health, management science, and education, and to examine university research contributions to well-being and community outcomes between 2015 and 2026. Findings provide evidence of a research map for impact pathways in the context of the Global South and low-resource settings. Community-based research that is participatory and policy-informed achieves better community results than top-down research. The North-South asymmetry in structures influences research agendas, with Global North institutions playing a major role in authoring studies based on empirical research from the Global South. Although models, frameworks, and tools from management science have proven effective in Nepal, Uganda, and Peru, they remain underutilized. Models, frameworks, and tools from management science that have proven effective in Nepal, Uganda, and Peru are underutilized. Closing the alignment-to-impact gap requires institutional reforms, including changes in research governance, partnership equity, and impact measurement. Future research needs to focus on community-embedded designs (longitudinal), community-based consortia (equal co-authorship), integration of management science tools in low-resource settings, and standardized metrics for well-being that measure objective and subjective community outcomes, as well as those in Scopus-indexed literature.